Cricopharyngeal myotomy in motor neurone disease. Issue 1 (January 1980) - Loizou, L A; Small, M; Dalton, G A
Abstract : Twenty-five patients with dysphagia caused by neurological disorders, mainly motor heurone disease, underwent cricopharyngeal myotomy. Nineteen patients showed slight to dramatic improvement of swallowing for variable periods of time. There were five postoperative deaths. The results indicate that this simple procedure is of benefit to a substantial proportion of patients with neurological causes of dysphagia.